Pengaruh Sistem Pajak, Keadilan Pajak, dan Love Of Money terhadap Persepsi Mahasiswa Akuntansi tentang Penggelapan Pajak (Tax Evasion) : (Studi Kasus pada Mahasiswa Prodi Akuntansi di Beberapa Perguruan Tinggi di Kota Kupang) - Maria Magdalena Data; Yohanes Demu; Yohana Febiani Angi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of the taxation system, tax justice, and love of money on accounting students' perceptions of tax evasion. The research was conducted on students of accounting study programs in several universities in Kupang City. The research approach used is quantitative with survey method. Data were collected through questionnaires distributed to 85 respondents selected using purposive sampling technique. Data analysis was performed with multiple linear regression using SPSS. The results showed that tax justice and love of money had a significant effect on students' perceptions of tax evasion, while the tax system had no significant effect. This finding indicates that students' perceptions of tax evasion are more influenced by perceptions of tax justice and personal orientation towards money, rather than an understanding of the tax system itself. Other results also show that simultaneously the tax system variables, tax justice and love of money have a joint effect on accounting students' perceptions of tax evasion. Therefore, the formation of fair perceptions and education of ethical values is important in minimizing the tendency to justify tax evasion.